(untitled) (Ustozlar uchun, 2025)
The rich culture and spiritual heritage of Uzbekistan are rooted in ancient Central Asian civilizations, the influence of the Great Silk Road, and Islamic traditions. This article explores various aspects of Uzbekistan’s culture, including architecture, art, customs, and Sufi teachings. Based on accurate and official sources, the article emphasizes the importance of preserving and efforts to preserve and develop the country’s invaluable heritage.